A Preliminary Study of the Effect of Supplementary Feeding on the Growth of Tridacna Maxima (Roding) (Bivalvia: Tridacnidae) - Estacion, Janet; Solis, Erwinia; Fabro, Lourdes (Silliman Journal, 2024)
The effect of supplementary feeding on the growth of - the giant clam Tridacna maxima was studied using Isochrysis galbana, Tetraselmis sp. anda mixture of both. Juvenile clams fed with the mixed culture had significantly higher growth rates, after the second and third ‘months, followed by Isochrysis and, Tetraselmis alone. Unfed ‘clams supplied with filtered seawater had the slowest growth.